Italian university students’ future time perspective and well-being during the COVID-19 pandemic - Parrello, Santa; Postiglione, Jacopo; Sica, Luigia Simona; De Rosa, Barbara; Parola, Anna; Regnoli, Giorgio Maria; Fenizia, Elisabetta; Sommantico, Massimiliano (Frontiers in Psychology, 2024)
During the COVID-19 pandemic, young adults worldwide showed signs of distress as they were affected in their specific developmental tasks, including the construction of personal and professional futures. The present study aimed to assess the situational future time perspective of Italian university students during the second pandemic wave, as measured by an ad hoc constructed instrument, to explore its interaction with some dispositional traits relevant in future construction, such as optimism, sense of life, aggression, and dispositional future time perspective, and to test their effect on psychological well-being. The total sample consisted of 389 subjects (18-35 years, M = 23.5, SD = 4.4). The results indicated that the pandemic experience, assessed by surveying specific indicators, negatively affected the future time perspective of students, particularly those dispositionally optimistic and convinced that life has meaning. However, awareness of the negative impact that the pandemic brought to the vision of the future seems to have dampened the levels of depression and stress, while anxiety was found to be related only to dispositional traits. The results also suggested the need for educational and economic policies that help young adults develop confidence in the future and in their ability to build it. with a potentially traumatic situation by cushioning its impact (Pfefferbaum et al., 2007;Rimé, 2020). The COVID-19 pandemic, which broke out in 2020, showed all the characteristics of a traumatic event of a collective nature, capable of negatively affecting psychological well-being and mental health. Indeed, increased levels of anxiety, depression, posttraumatic symptoms, compulsive behaviors, and social isolation have been reported in individuals of all ages in countries around the world (e.g.,